Food and nutrition education in Australian primary schools: parents' views. Issue 4 (12th May 2021) - Aydin, Gozde; Booth, Alison; Margerison, Claire; Worsley, Anthony
Abstract : Purpose: Primary schools provide continuous, intensive contact with large numbers of children starting from a young age, thus providing an appropriate setting for the promotion of healthy eating through food and nutrition education (FNE). This qualitative study explores the views of Australian primary school parents about FNE in primary schools. Design/methodology/approach: In total, 19 parents of primary school children from Victoria participated in semi-structured interviews. Audio recordings were transcribed and underwent thematic analysis using Nvivo. A total of three themes emerged: FNE topics currently taught in primary schools, essential food skills and knowledge for primary school children and the importance of FNE. Findings: Most parents thought that FNE is as important as the core subjects of primary school. Parental support for FNE, which is delivered over a prolonged period, and expanded by hands-on content such as cooking and gardening classes was evident. Parents viewed these classes as likely to improve children's food-related knowledge and healthy eating behaviours. Parents expressed appreciation for schools' emphasis on food sustainability and its alignment with school policies and practices. Parents were keen to see more sustainability included in the curriculum. Practical implications: These results may have implications for curriculum developers and schools, as the findings can assist the design of food and nutrition curricula for primary schools which can empower children as well as their families to make better food-related decisions. Originality/value: Australian parents' views of FNE in primary schools have been under examined.